Navigation systems and 3D imaging in percutaneous nephrolithotripsy: improving outcomes and safety - Bouchalakis, Athanasios; Somani, Bhaskar Kumar; Lima, Estevao; Rassweiler-Seyfried, Marie-Claire; Mamoulakis, Charalampos; Tokas, Theodoros (Current opinion in urology, 2024)
Purpose of review - Percutaneous nephrolithotripsy (PCNL) is the first-line management option for large kidney stones (>2 cm). It remains, however, a demanding procedure with considerable morbidity. The present narrative review summarizes recent knowledge from original research studies investigating navigation systems/three-dimensional (3D) imaging in PCNL, particularly on publications during the past 12-18 months. - Recent findings - Navigation systems and 3D imaging are primarily used for preoperative planning, with few intra-operative applications. Patient management and residents’ training could benefit from their use. - Summary - Navigation systems and 3D imaging technology have emerged as a potential game-changer in PCNL. Even though available evidence is currently scarce/inconclusive, the safety/efficacy of navigation systems and 3D dimensional imaging use in PCNL appears promising. This advanced technology offers precise anatomical mapping, improved visualization, and surgical accuracy. Enabling a comprehensive preoperative evaluation and improving guidance, navigation systems, and 3D imaging technology may improve the safety and efficacy of PCNL. With continuous technological evolution, it is expected that improvements/innovations will offer further aid in such demanding procedures. Familiarization and cost reduction are necessary for widespread application, while larger-scale prospective studies and well designed randomized controlled trials are still needed.
Gesehen am 09.01.2025